Course recommendation as a construct in student evaluations: will students recommend your course?. Issue 6 (3rd June 2018) - Ang, Lawrence; Breyer, Yvonne Alexandra; Pitt, Joseph
ABSTRACT: Recommendation is a highly credible and powerful construct in marketing. This article investigates the construct intention to recommend in the context of student evaluations of teaching. Motivated by changes in the sector, the study explores what factors drive course recommendation and their relationship with each other. A structural model is tested, using partial least squares on a sample of 113 students. The results show that both emotional (i.e. joy of learning) and cognitive (i.e. course value) factors influence intention to recommend . These two driving factors are more likely to occur if the course can bridge theory and real-world practice. The approach to understanding what drives course recommendation opens up new avenues of research. It proposes to expand the traditional model of student evaluations of teaching to one which includes course value in the context of a competitive education sector.